Sleep and Epilepsy Link by Plasticity - Halász, Péter; Szűcs, Anna (Frontiers in Neurology, 2020)
We aimed to explore the link between NREM sleep and epilepsy. Major childhood epilepsies offered us good models to study. Mesiotemporal lobe epilepsy, absence epilepsy and human perisylvian network epilepsies are epileptically transformed systems. This approach allows a system-based taxonomy instead of the outworn generalized-focal classification. Medial temporal lobe epilepsy links to the memory-system, where epileptic transformation results in a switch of normal sharp wave-ripples to epileptic spikes and pathological high frequency oscillations, compromising sleep-related memory consolidation. Absence epilepsy (AE) and juvenile myoclonic epilepsy (JME) belong to the corticothalamic, system. The burst-firing mode of NREM sleep normally producing sleep-spindles turns to an epileptic working mode ejecting bilateral synchronous spike-waves. There seems to be a continuity between the two conditions, AE progressing sometimes to JME. The common absences and the similar bilateral synchronous discharges in both conditions, support this continuity, while the continuous age windows- AE in schoolchildren, JME in adolescence-, and the increased excitability in JME compared to AE suggest a progress. In perisylvian network epilepsies - idiopathic focal childhood epilepsies and malignant electrical status epilepticus in sleep including Landau-Kleffner syndome - centrotemporal spikes turn epileptic, with the potential to cause cognitive impairment. Postinjury epilepsies modelled by the isolated cortex model parallel the pathomechanism of the above epilepsies suggesting the derailment of homeostatic plasticity as a common step of epileptogenezis. NREM sleep participates in epileptogenezis providing templates for plasticity. This sleep-origin explains epileptiform discharges’ link with NREM sleep slow oscillations, spindles and ripples. Normal synaptic plasticity erroneously overgrowing homeostatic processes may derail toward an epileptic working-mode manifesting the involved system’s features. The impact of NREM sleep is unclear in epileptogenezis occurring in adolescence and adulthood, when plasticity is lower. The epileptic process interferes with homeostatic synaptic plasticity and may cause cognitive impairment. Its type and degree depends on the affected network’s function. We hypothesize a vicious circle between sleep end epilepsy. The epileptic derailment of normal plasticity interferes with sleep cognitive functions. Sleep and epilepsy interconnect by the pathology of plasticity.